Śladami biblijnego marzēaḥ (Amos 6, 7; Jeremiasz 16, 5) - Tryl, Fabian (The Biblical Annals, 2017)
The mysterious term „marzeah” occurs twice in the Old Testament. In the Book of Amos it stands for an aristocratic feast, whereas in the Book of Jeremiah we read about „the house of marzeah” meaning a place used for mourning for the dead. The texts from Ugarit provide us with more information. Thorough analysis of the texts implies that „marzeah” was an institution assembling people representing upper social classes. At least one of its aims was cult of the dead. It clearly resembles mesopotamian „kipsu” – a ritual feast where people called their ancestors to „eat bread and drink water”. In the Bible it is a clear example of the trait of pagan beginnings of Israel, whose elements in their fragmentary form lasted until VI century B.C.